2018
DOI: 10.1021/acs.jpcc.8b01610
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Quenching-Based Evaluation of Glucose Oxidase Composite with Conducting Polymer, Polypyrrole

Abstract: Glucose oxidase (GOx) composites with conducting polymers (e.g., polypyrrole (Ppy)) are excellent nanobiomaterials suitable for the design of bioelectronic devices such as biosensors and biofuel cells. Here, we address the spectroscopic properties of GOx, flavin adenine dinucleotide (FAD), and composites of these compounds with polypyrrole (Ppy). The exploration of native GOx and FAD solutions confirmed that about 5% of FAD dissociated from GOx during the period of solution preparation, and this fraction remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…The majority of computational studies on FAD in the past have been dedicated to flavoproteins with FAD adopting T-shaped and other "open" geometries, the "stacked" geometry of FAD has not yet been the subject of those studies. The recent publication of Bubniene et al [16] reflects this gap. According to Bubniene et al differences in the FAD and polypyrrole average fluorescence relaxation time showed that the FAD composite with polypyrrole effectively quenched the FAD fluorescence since FAD could not freely unfold in this environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of computational studies on FAD in the past have been dedicated to flavoproteins with FAD adopting T-shaped and other "open" geometries, the "stacked" geometry of FAD has not yet been the subject of those studies. The recent publication of Bubniene et al [16] reflects this gap. According to Bubniene et al differences in the FAD and polypyrrole average fluorescence relaxation time showed that the FAD composite with polypyrrole effectively quenched the FAD fluorescence since FAD could not freely unfold in this environment.…”
Section: Discussionmentioning
confidence: 99%
“…The model of Li et al [13,14] has been adopted by Sengupta et al [15] in their investigation of pH-dependent dynamic behavior of FMN and FAD on a femtosecond to nanosecond time scale. More recently the pH-depending prevalence of the stacked form of FAD proposed by Li et al [13] has been used as a model concept in the publication of Bubniene et al [16] about the fluorescence quenching-based evaluation of a glucose oxidase composite with a conducting polymer-polypyrrole: The stacked form of FAD is thought to be responsible for the fast quenching of the FAD fluorescence, which could not unfold freely in this specific environment as the authors stated.Despite theoretical studies which include lumiflavin, riboflavin and FMN as a model of FAD-flavoprotein interactions in proteins [17][18][19][20], theoretical studies of the stacked form of FAD as well as studies of the unfolding process from the closed to the open conformer are still missing. The present work aims to fill this gap.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sensing features of the reaction rate have been used from the very beginning of the electroanalytical methodologies (polarographic, voltammetric, chronoamperometric, etcetera) to determine the concentration of the analyte reacting either, directly on any non‐reactive electrode or indirectly through an enzyme or an catalyst adsorbed on the electrode …”
Section: Reaction Rate and Reaction Energy Respond To And Sense Thementioning
confidence: 99%
“…The sensing features of the reaction rate have been used from the very beginning of the electroanalytical methodologies (polarographic, voltammetric, chronoamperometric, etcetera) to determine the concentration of the analyte reacting either, directly on any non-reactive electrode [8] or indirectly through an enzyme [9] or an catalyst adsorbed on the electrode. [10][11][12] Recently, this sensing principle has been reconsidered and generalized by our research group substituting the passive electrodes by electroactive electrodic materials constituted by multistep molecular machines and studying how the energy consumed by the electrodic reaction is influenced by the different physical or chemical working conditions.…”
Section: Reaction Rate and Reaction Energy Respond To And Sense Thementioning
confidence: 99%